Construction of a series of metal–organic frameworks based on novel flexible ligand 4-carboxy-1-(3, 5-dicarboxy-benzyl)-pyridinium chloride and selective d-block metal ions: crystal structures and photoluminescence1. Issue 33 (7th September 2015) - Li, Hai-Yang; Cao, Li-Hui; Wei, Yong-Li; Xu, Hong; Zang, Shuang-Quan
<x xml:space="preserve">Abstract</x> Seven novel supra-architectures based on a novel flexible multi-carboxylate chloro-inner-salt ligand are prepared through a hydrothermal method.